Which children with otitis media acuta benefit from treatment with antibiotics? An individual patient data meta-analysis - Rovers, M; Glasziou, P; Appelman, C; Burke, P; McCormick, D; Damoiseaux, R; Gaboury, I; Little, P; Hoes, A (2006)
Background: At present it is not known which subgroups of children with otitis media acuta (AOM) derive benefit from antibiotics and which do not. Methods: In an individual patient data meta-analysis on six randomised trials, including 1643 children aged 6 months to 12 years with AOM, we performed subgroup analyses to identify children who might benefit more than others from treatment with antibiotics. The primary outcome was a prolonged course of AOM, which was defined as having either residual pain or fever at 3-7 days. Results: In children younger than 2 years of age with bilateral AOM, 55% in the control group and 30% in the antibiotics group still had pain and/or fever at 3-7 days: a rate difference (RD) of -25% (95% CI -36 - -14%, NNT 4). In children aged 2 years or older with unilateral AOM these percentages were 26% and 19% (RD -7%, 95% CI -14-0%, NNT 15). For age alone no differences were found. In children with and without otorrhoea the RD and NNT were -36% (95% CI -53 - -19%) and 3, and -14% (95% CI -23% - -5%) and 8. Discussion: Antibiotics appear to be more beneficial in children younger than 2 years of age with bilateral AOM, and in children with AOM and otorrhoea. For most other children with mild disease an observational policy seems justified. The Dutch AOM guideline has been changed to match these findings.